Study of the Morphological Characteristics of the Human Gallbladder in Relation to Age and Sex of Bangladeshi People - Rahman, Khalilur; Akhter, Afruza Bulbul; Anwar, Selina; Begum, Anjum Ara; Ahmed, Sultan; Saha, Narayan Chandra (Bangladesh Journal of Anatomy, 2014)
Context: Variations in the morphology of the gallbladder have long been debated by the abdominal surgeons. So it is important for the surgeons to appreciate the possible anatomical variations that can be encountered during surgery to prevent post operative complications during cholecystectomy. This study was aimed at to find out any variations in the morphology of the postmortem gallbladder in adult Bangladeshi male and female to find out any difference in the gallbladder morphology in relation to age and sex. Material & methods: This study was done on sixty (60) human postmortem gallbladder from Bangladeshi male and females of two age groups- group A age between 20-40 years and group B age between 41-65 years. Among the morphological parameters length, breadth, thickness and volume of the gallbladders were measured. Result: Result of the present study showed that the mean values of gross morphological features of the gall bladder (length, breadth, thickness, volume & weight), were higher in group B than group A except the thickness in female which show somewhat higher mean value in group A than group B. The result showed significantly high value for length and volume in case of male only (p<.05) in group B than group A. When comparison were made between these values in regard of sex, it was found that males of group B showed higher mean value for all parameters than females of group B and result showed a significantly higher value for the length of gallbladder(p<.05). But in case of group A, whereas male had higher mean value for length and weight and, female had higher mean value for breadth, thickness and volume though no values were significantly different. Conclusion: The higher mean values of different parameters of the gallbladder in elderly males and also from their female counterparts of the same age groups may be due to shorter size of the females. Again some parameters showed higher values in females (breadth, thickness and volume) which may indicate the predominance of cholelithiasis in females. Again most of the values in male and female of elderly were higher than the younger groups indicate the formation of gallstones in elderly. DOI: http://dx.doi.org/10.3329/bja.v11i2.20676 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 81-85